Development and Validation of RP-HPLC Method for Simultaneous Estimation of Metformin Hydrochloride, Linagliptin and Dapagliflozin in Synthetic Mixture - Munazza Iqbalahmed Shaikh; Amar M. Raval (Asian Journal of Pharmaceutical Research and Development, 2026)
A simple, accurate, precise, and reproducible reverse phase high-performance liquid chromatography (RP-HPLC) method was developed and validated for the simultaneous estimation of Metformin (MET), Linagliptin (LINA), and Dapagliflozin (DAPA) in a synthetic mixture. Chromatographic separation was achieved using a Shimadzu LC-2030 HPLC system equipped with a C18 column (250 mm × 4.6 mm, 5 µm particle size). The optimized mobile phase consisted of Methanol:10 mM phosphate buffer (pH adjusted to 4 using orthophosphoric acid) in the ratio of 65:35 (% v/v), delivered at a flow rate of 1.0 mL/min, and detection was carried out at 232 nm. The retention times were found to be 2.337 min for Metformin, 3.324 min for Linagliptin, and 12.874 min for Dapagliflozin. The method demonstrated good linearity in the concentration range of 2.5-15 µg/mL for all three drugs, with correlation coefficients of 0.9969 for Metformin, 0.9944 for Linagliptin, and 0.9938 for Dapagliflozin. Recovery studies showed percentage recoveries of 102.89%, 99.20%, and 101.50% for Metformin, Linagliptin, and Dapagliflozin, respectively. The developed method was validated according to International Council for Harmonisation guidelines for specificity, linearity, accuracy, precision, robustness, limit of detection (LOD), and limit of quantification (LOQ). The results indicated that the proposed method is simple, sensitive, accurate, and suitable for routine quality control analysis for the simultaneous estimation of Metformin, Linagliptin, and Dapagliflozin in pharmaceutical dosage forms.